Challenges Faced by U.S. Veterinary Technicians in the Workplace During COVID-19 - Rowe, Zoe C.; Drewery, Merritt L.; Anderson, Ryan G.; Russo, Crystal M. (Frontiers in Veterinary Science, 2022)
During COVID-19, the demand for veterinary technicians increased due to increased animal care appointments booked, decreased worker productivity, pandemic-related staffing shortages, and adapted methods of care delivery. Research has been conducted to assess the effect of the COVID-19 pandemic on educators and human healthcare workers, but there is a lack of literature on veterinary technicians, the animal healthcare equivalent of nurses. The objective of our study was to evaluate how COVID-19 affected veterinary technicians. We distributed an electronic researcher-developed survey-based instrument to veterinary technicians working in the U.S. during COVID-19. We received 1,132 usable responses. Descriptive statistics were analyzed using SPSS 26.0. Our respondents were overwhelmingly female (97%) and mostly employed full-time (87%) in a companion animal practice (61%). A majority of respondents reported COVID-19 had a large effect (45%) or completely dominated the work (12%) at their practice. While 52% of respondents felt their efforts during COVID-19 were appreciated, only 43% agreed or strongly agreed their hours were manageable. Support staff availability was completely or barely adequate for 42% of respondents and personal protective equipment was mostly or completely adequate for 60% of respondents. The greatest professional challenges during COVID-19 were being treated worse by animal owners and difficulty communicating with clients (53% and 16% of respondents, respectively). There have been few efforts to document the professional environment experienced by veterinary technicians during COVID-19. This is critical as pre-pandemic data indicate veterinary technicians are high-risk for professional burnout and COVID-19 placed additional burdens on essential workers.